2013
DOI: 10.1175/jcli-d-12-00030.1
|View full text |Cite
|
Sign up to set email alerts
|

The Influence of Stratospheric Vortex Displacements and Splits on Surface Climate

Abstract: A strong link exists between stratospheric variability and anomalous weather patterns at the earth's surface. Specifically, during extreme variability of the Arctic polar vortex termed a ''weak vortex event,'' anomalies can descend from the upper stratosphere to the surface on time scales of weeks. Subsequently the outbreak of cold-air events have been noted in high northern latitudes, as well as a quadrupole pattern in surface temperature over the Atlantic and western European sectors, but it is currently not… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

22
324
4

Year Published

2013
2013
2017
2017

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 242 publications
(350 citation statements)
references
References 37 publications
22
324
4
Order By: Relevance
“…We did not find statistically significant differences in compositing between vortex-splitting or displacement events in either the 2 or ΔLOD anomalies, even though previous studies have shown significant differences in the precursor anomaly patterns associated with vortex splits and displacements [Martius et al, 2009;Mitchell et al, 2012]. The difference in the Earth rotation signature of these types of events and a possible…”
Section: Discussioncontrasting
confidence: 79%
See 1 more Smart Citation
“…We did not find statistically significant differences in compositing between vortex-splitting or displacement events in either the 2 or ΔLOD anomalies, even though previous studies have shown significant differences in the precursor anomaly patterns associated with vortex splits and displacements [Martius et al, 2009;Mitchell et al, 2012]. The difference in the Earth rotation signature of these types of events and a possible…”
Section: Discussioncontrasting
confidence: 79%
“…The surface pressure signals preceding SSWs differ between vortex-displacement and vortex-splitting events, with vortex displacements more strongly associated with a low-pressure anomaly over North America, a high-pressure anomaly over Western Europe, and North Atlantic blocking, and vortex splits associated with high-pressure anomalies over the North Pacific and Siberia, a low-pressure anomaly over the North Atlantic, and North Pacific blocking with or without Atlantic blocking [Martius et al, 2009;Mitchell et al, 2012]. The surface anomaly pattern preceding vortex displacements is more closely associated with a wave 1 pressure anomaly (which would result in a negative M 2 anomaly), whereas vortex splits can be preceded by a wave 1 or wave 2 anomaly [Bancalá et al, 2012;Martius et al, 2009] (a wave 2 anomaly results in no net M 2 excitation), though this relationship seems to be strongly modulated by the phase of ENSO [Barriopedro and Calvo, 2014].…”
Section: Polar Motion Anomalies Preceding Sswsmentioning
confidence: 99%
“…In particular, improvements of the microbarom predictions would require more accurate source and propagation models [e.g., Landès et al, 2014]. With the increasing number of IMS and other infrasonic arrays deployed around the globe, more systematic studies using historical infrasound data set and state-of-the-art reanalysis systems could provide useful information on the polar vortex structure and the longer-term influences of SSWs on the troposphere [e.g., Charlton-Perez et al, 2007;Mitchell et al, 2013;Smets and Evers, 2014].…”
Section: 1002/2015jd023273mentioning
confidence: 99%
“…20). SSW events are often followed by a negative phase of the AO at the surface with a time lag of 1 or 2 months [21][22][23] . This indicates that understanding possible contributors to recent stratospheric variability, which may include cryospheric changes 24 , is critical for the better understanding of the surface climate variability in the recent past.…”
mentioning
confidence: 99%